Isolated Inferior Rectus Muscle Entrapment following Endoscopic Sinus Surgery. (2nd July 2018) - Shapiro, Scott; Schaefer, Jamie L.; Gupta, Sumeet; Nguyen, John; Kellermeyer, Brian
Abstract : Orbital complications are known risks of endoscopic sinus surgery (ESS). The lamina papyracea and medial rectus muscle are the most commonly injured structures during ESS. Inferior rectus injury is more rare, with only one reported case of isolated inferior rectus injury in the literature. Guidelines for managing ESS-induced inferior rectus injury do not exist, and delayed intervention and management of adjacent sinuses may affect long-term outcomes such as persistent diplopia and disfigurement. In this report, we present a case of a 67-year-old man with diplopia due to isolated left inferior rectus muscle entrapment and injury from violation of the orbital floor during previous ESS. We postulate that an incomplete maxillary antrostomy contributed to scar band formation and entrapment of the inferior rectus muscle after the orbital floor was violated, and advocate early intervention with a wide, complete maxillary antrostomy if the orbital floor is injured during ESS.